Empirical nursing : the art of evidence-based care - Garrett, Bernie (Emerald Publishing Limited, 2018)
This book seeks to provide students and practicing nurses with the tools to better understand and engage in scientific arguments to support quality nursing and evidence-based practice. The nature of nursing and its relationship with science remains an area of ongoing debate, controversy and considerable confusion to both students and practitioners. For a science-based health discipline, it is something of a paradox that most nursing students have limited exposure to scientific philosophy education, which is not covered in depth in many modern university nursing programmes. This work seeks to remedy this: in providing material on modern scientific research methods, with particular emphasis on the context of practice, it presents an alternative theoretical iteration of holistic nursing as scientific inquiry. The author is a passionate advocate for empirical and pragmatic approaches to nursing, and the book provides challenging ideas to support a new wave of critical-thinking in contemporary nursing, confronting postmodern dogma with contemporary scientific critique. In doing so, this text engages readers with the art of progressive empirical client-centred care, appropriate for the development of 21st century holistic nursing practice.